Cybernetic Tthinking: Serealist and Wholist style as an English Grammar Pproblem Ssolving Learning Pperspective during a pandemic - Ferri Susanto; Ali Khan; Changjiang Deng; Kaufmann Cardinal (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2022)
This study aims to describe the way of thinking of cybernetics students with Serialist and wholist thinking styles to solve English grammar problems. The study used a qualitative approach, so the data collection techniques used questionnaires and instruments in the form of tests of English grammar questions and interviews. Implementation of research at the Faculty of English Tarbiyah in the second semester of Fatmawati Sukarno State Islamic University Bengkulu in the 2020/202 academic year. The research sample used a purposive sampling technique, namely two students with a serialist thinking style and two students with a holistic thinking style. The results showed that the question information received by Serialist and wholist thinking style students entered the five senses directly through the senses of sight and hearing. The process of attention occurs after the questions are read and understood so that perceptions arise as concepts that are needed from long-term memory to solve problems. At the time of reunion, serialist thinking style students are very risky to improvise. While students with a wholist thinking style, the concepts needed in short-term memory are not stored properly by long-term memory, so these students often experience mistakes and forget when doing retrieval; as a result, these students are more likely to generalize excessively. These two thinking styles are expected to be able to become perspectives on the development of thinking styles in the teaching and learning process during the current pandemic.